ANALISIS PERILAKU AKADEMIK SISWA KELAS 10 DI SMA 7 MEDAN - Rivanti Br Sinuraya; Kesia Simanjuntak; Elza Tiurmaida Rimmauli Silalahi; Arlia Ananta Salsabila (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the academic behavior of class X HAMKA students at SMA Negeri 7 Medan, which is not only measured through report card grades, but also through aspects of learning motivation, self-efficacy, learning habits, learning orientation, and environmental factors. This study uses a descriptive quantitative approach with a data collection technique in the form of a Likert scale questionnaire consisting of 20 statements. The research sample consisted of 30 students with a total sampling technique. The data were analyzed using descriptive statistics to obtain a general overview of student academic behavior. The results of the study showed that overall student academic behavior was in the high category with an average percentage of 75.2%. A total of 26 students were in the high category and 4 students were in the very high category. Student responses were dominated by positive answers indicating that most students had good learning motivation, self-confidence, learning habits, and environmental support in supporting the learning process. However, some students still showed a tendency towards less than optimal academic behavior, such as procrastination, lack of learning discipline, and learning that was still oriented towards grades. The findings of this study indicate that student academic behavior cannot be assessed only through report card grades, but needs to be understood more comprehensively through various aspects of learning behavior. Therefore, schools, teachers, and parents are expected to provide optimal support in fostering positive academic behavior in students, thereby making the learning process more effective and meaningful.